2020
DOI: 10.6023/a20050145
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Charge Transfer Plasmon at Gold/Copper Heterointerface

Abstract: Metal nanostructures with localized surface plasmon resonance (LSPR) have attracted great attention in catalysis, sensing, nanooptics, and nanomedicine. Charge transfer plasmon (CTP) is a LSPR mode that strongly depends on a conductive junction between metallic nanounits. Benefitting from the charge transfer junction, CTP provides a facile way to generate widely tunable LSPR with highly localized/enhanced light magnetic field and photothermal effect. The limited availability of highly tunable CTP structures an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
(44 reference statements)
1
6
0
Order By: Relevance
“…A twin defect and stacking fault were found to exist at the twinned Au nanotips, which led to Cu atoms being deposited on the twinned nanotip. In addition, Deng’s group developed width-adjustable Au–Cu Janus nanostructures by fish sperm DNA ( Figure 3E ) ( Zhu et al, 2020 ). The strategy relied on the non-specific surface adsorption of fish sperm DNA onto an Au nanoparticle to control heterogeneous Cu nucleation, which had low-cost and natural advantages.…”
Section: Synthesis Of Au–cu Nanostructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…A twin defect and stacking fault were found to exist at the twinned Au nanotips, which led to Cu atoms being deposited on the twinned nanotip. In addition, Deng’s group developed width-adjustable Au–Cu Janus nanostructures by fish sperm DNA ( Figure 3E ) ( Zhu et al, 2020 ). The strategy relied on the non-specific surface adsorption of fish sperm DNA onto an Au nanoparticle to control heterogeneous Cu nucleation, which had low-cost and natural advantages.…”
Section: Synthesis Of Au–cu Nanostructuresmentioning
confidence: 99%
“…(D) HAADF-STEM image and SEM image of Au–Cu Janus nanojellyfish ( Mi et al, 2022 ). (E) TEM images of Au–Cu heterodimers ( Zhu et al, 2020 ). (F) Schematic illustrating the synthesis of Au–Cu Janus nanostructures ( Fan et al, 2022 ).…”
Section: Synthesis Of Au–cu Nanostructuresmentioning
confidence: 99%
“…The latter relies on solvent-induced double-layer neutralization and dehydration to realize DNA-directed NP coupling. To further enable a charge transfer between the coupled NPs, thermal/optothermal sintering or chemical welding can be adopted. While these processes are highly effective, some challenges exist. First, AIS brings hard-to-remove Ag + contaminants to the NP surface, which adds great uncertainties to surface-dictated processes.…”
Section: Introductionmentioning
confidence: 99%
“…The strongly coupled nanoassembly behaves like a "nanomolecule" where a slight structural alteration dramatically modies its behaviors. [13][14][15][16][17][18] Localized surface plasmon resonance (LSPR) originating from light-induced collective electron oscillations in a metal nanostructure provides an ideal system to study subwavelength electromagnetic interactions. [19][20][21] We previously revealed that silver ion or less-polar solvents can induce strong plasmon coupling in DNA-tethered gold nanoparticle (AuNP) homodimers.…”
Section: Introductionmentioning
confidence: 99%